Entry mechanism, trafficking and localisation of Macrobrachium rosenbergii (De Man, 1879) nodavirus in SF9 insect cells - Hanapi, Ummi Fairuz (2015)
Macrobrachium rosenbergii nodavirus (MrNv) is a Gammanodavirus that was isolated from infected giant freshwater prawn juveniles. MrNv is the major cause of white tail disease (WTD) in prawn hatcheries and the mortality of the infected post-larvae is 100% in just 3 days. Vertical transmission and widen host range contribute to a worldwide economical crisis. No effective treatments are available to stop the virus infection. This study was aimed to identify the trafficking mechanism involved in MrNv infection and its localisation in the infected cells by using the virus-like particles (VLPs) of MrNv. The RNA2 of MrNv that codes for the viral capsid was previously cloned into pTrcHis2-TOPO expression vector. The recombinant MrNv capsid (MrNvc) protein with the size of about 46 kDa produced VLPs in Escherichia coli with undistinguishable properties from the native MrNv. These VLPs were used to study the entry mechanism, trafficking and localisation of the MrNv in Sf9 insect cells. Live cell observation using the live cell imaging system (LCIS) revealed that the internalisation of MrNvc VLPs was initiated by VLPs binding to the cell surface. Ammonium chloride inhibition study and LCIS showed that the MrNvc VLPs entry was mediated by acidic endosomal pathway. The number of the green fluorescent granules in Sf9 cells incubated with MrNvc VLPs decreased in the presence of 0.1 mM and 1.0 mM NH4Cl which blocks the endosomal acidification. From LCIS data, green fluorescent ‘ring-like shape’ was observed as a result of attached VLPs being accumulated around the membrane pits. Green granules of endosomes enclosing VLPs were produced and later, the shape and size of the endosomes become disproportionate. The VLPs escape from the endosomal membrane when the fluorescent green granules faded and disappeared. MrNvc VLPs localised in the cell cytoplasm and nucleus as spotted from the Z-stack images of the fluorescence microscopy and the Western blotting of the Sf9 sub-cellular fractionation. His-tag located at the C-terminal end of the MrNvc can still be detected by anti-His antibody suggesting that MrNvc is still intact upon internalisation and nuclear translocation. The mutants of the N-terminally truncated capsid proteins [9ΔMrNvc, 19ΔMrNvc 29ΔMrNvc and (20-29)ΔMrNvc] were used to study the function of the N-terminal residues in nuclear translocation. The 29ΔMrNvc and (20- 29)ΔMrNvc without the positively-charged RNA-binding region (20KRRKRSRRNR29) showed no effect in VLPs entry into Sf9 cells but these mutants were found much lesser in the cell nucleus. This study revealed that MrNvc internalised Sf9 cells by receptor-mediated endocytosis and localised in the cell cytoplasm and nucleus. The endosomal escape mechanism of MrNv is different from that of Flock House virus (FHV), a model for non-enveloped virus entry, which involves gamma (γ) peptide cleavage at the C-terminal end of its capsid protein. It is suggested that 20KRRKRSRRNR29 sequence has dual function as RNA-binding sequence and nuclear targeting sequence of MrNv. This close up examinations on the cellular level of MrNv infection will contribute to its elimination and control in giant freshwater prawn farming. Understanding the mechanism involved in MrNvc VLPs internalisation, trafficking and localisation in its host’s cell will be useful for other studies such as drug nano-delivery, gene transfer and vaccine development.